2019
DOI: 10.4103/jispcd.jispcd_333_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inhibition of mineral loss from human tooth enamel by carbon dioxide laser and 1.23% acidulated phosphate fluoride

Abstract: Aims and Objectives: The efficacy of carbon dioxide (CO 2 ) laser irradiation combined with fluoride in inhibiting enamel demineralization has been demonstrated by several laboratory investigations. However, there are very few reports about the in situ or in vivo caries preventive effect of CO 2 laser combined with topical fluoride on dental enamel. Hence, an in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Silva et al [ 34 ] assessed the effect of some products containing fluoride (i.e., titanium tetrafluoride and stannous fluoride) alone and in combination with CO 2 laser on enamel erosion [ 34 ]. Another study revealed that beneficial effects were obtained when acidulated phosphate fluoride was used along with CO 2 laser irradiation [ 35 ]. Evidence shows that CO 2 laser irradiation may block the dentinal tubules by dentin melted due to high temperature at the irradiation site.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al [ 34 ] assessed the effect of some products containing fluoride (i.e., titanium tetrafluoride and stannous fluoride) alone and in combination with CO 2 laser on enamel erosion [ 34 ]. Another study revealed that beneficial effects were obtained when acidulated phosphate fluoride was used along with CO 2 laser irradiation [ 35 ]. Evidence shows that CO 2 laser irradiation may block the dentinal tubules by dentin melted due to high temperature at the irradiation site.…”
Section: Discussionmentioning
confidence: 99%
“…Another three ex-vivo studies [20][21][22][23] that used CO 2 laser were included. The data included in the metaanalysis were considered continuous.…”
Section: Heterogenicity and Meta-analysismentioning
confidence: 99%
“…Two studies [14,24] performed enamel surface profilometry. Also, three studies performed Polarized light microscopy to evaluate enamel lesion depth in um but one of these studies tested one specimen as qualitative assessment only [20,21,23].…”
Section: Heterogenicity and Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This agent has been successfully used in preventive dentistry for a number of years for the prevention of dental caries and dental erosion. [ 15 16 ]…”
Section: Introductionmentioning
confidence: 99%